Visiones y visitas de Torres con don Francisco de Quevedo por la Corte - Torres Villarroel, Diego de, 1693?-1770 (Diferencias., 2019)
Based on the style of Francisco de Quevedo's Sueños, the author joins Quevedo in his dreams where they have various adventures and criticize lawyers, doctors, and the morality of the period.